Borders and Boundaries: Importing Asset Recovery "Duty Free" in Transitional Justice Processes - Maguchu, Prosper (Indonesian Journal of International Law, 2020)
As new conflicts emerge, transitional justice practitioners are finding it increasingly imperative to incorporate the concepts of asset recovery into transitional justice processes and mechanisms. However, for its success, the pillar of transitional justice relating to international asset recovery needs strengthening. Yet a granular understanding of this dimension remains a critical blind spot in the transitional justice and human rights conversation. This paper brings the dynamics of asset recovery as an emerging aspect of human rights law to the fore. In terms of methodology this paper relies on Sharp’s critically motivated problem-solving theory. The paper suggests that for transitional justice to be holistic it should include asset recovery in its accountability mechanisms. Hopefully, it humbly contributes a new angle toward the understanding of what transitional justice can and could become.